The Restoration and Renovation of the St. Louis Post Office/Custom House, St. Louis, Missouri - Patty Berkebile Nelson Associates (Oz, 1982)
The St. Louis Post Office/Custom House (1873-1889, Alfred B. Mullet) would get an almost perfect score on any preservationist's worthiness test. The building is stylistically important and typologically significant…